Plany zawodowe studentów specjalności rachunkowość i auditing Akademii Ekonomicznej im. Oskara Langego we Wrocławiu a ich kwalifikacje i predyspozycje. Wnioski z przeprowadzonych badań - Nowak, Marta (Professional Plans of Auditing and Accounting Students at Oscar Lange University of Economics Versus their Qualifications and Predispositions. Research Outcome, 2005)
The article consists of the analysis from the questionnaire research which was conducted on the accounting and auditing students at the Oscar Lange University of Economics. It focused on the planned career paths, possessed qualifications, predispositions and acquired work practice of the students. It confronts their job plans with their possibilities. The research also identifies the most attractive jobs for those who major in accounting and auditing and also the sectors for those who declare they will conduct their own business in the future.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 130-136